Equilibrium of Groundwater with Carbonate Minerals of the Water-Bearing Rocks under Anthropogenic Impact (by the example of Kishinev, Moldova); IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Timoshenkova A. N. (Hydrogeochemistry and Hydrogeoecology, 2014)
Title screen